Autologous Cells for Kidney Bioengineering - Wilm, Bettina (Curr Transplant Rep, 2016)
Worldwide, increasing numbers of patients are developing end-stage renal disease, and at present, the only treatment options are dialysis or kidney transplantation. Dialysis is associated with increased morbidity and mortality, poor life quality and high economic costs. Transplantation is by far the better option, but there are insufficient numbers of donor kidneys available. Therefore, there is an urgent need to explore alternative approaches. In this review, we discuss how this problem could potentially be addressed by using autologous cells and appropriate scaffolds to develop ‘bioengineered’ kidneys for transplantation. In particular, we will highlight recent breakthroughs in pluripotent stem cell biology that have led to the development of autologous renal progenitor cells capable of differentiating to all renal cell types and will discuss how these cells could be combined with appropriate scaffolds to develop a bioengineered kidney.